Quantifying Feel, Fragrance And Finish: A Review of Sensory Threshold In Cosmetics - Suryaneta Suryaneta; Kiki Fibrianto (CV. Inara, 2025)
Sensory experience determines whether cosmetic products are adopted, repurchased, and trusted. Yet the knowledge needed to set defensible sensory targets is scattered across psychophysics, descriptive analysis, and category-specific practice. This review consolidates the concept of “thresholds” for cosmetics and explains how to use them to guide formulation, quality control, and claims. Author define detection and recognition thresholds as performance-based points on a psychometric function that ensure key notes and tactile cues are truly perceivable and correctly identified. Author then describe the difference threshold, or just noticeable difference, as the smallest reliable change from a reference and show how JNDs translate directly into specification bands that control batch-to-batch drift. Because perceptibility does not guarantee liking, we integrate consumer-facing acceptance and rejection thresholds to locate intensity regions that preserve preference and avoid penalties in market. Methodologically, the review emphasizes bias-resistant forced-choice designs, supported by adjustment and categorical procedures, and shows how threshold estimation aligns with descriptive sensory programs already used for creams and lotions across realistic stages of use. Taken together, these tools provide a practical bridge from small compositional or process changes to user-relevant discriminability and acceptance. Author conclude with priorities for practice, including disciplined panel management, tighter linkage between laboratory thresholds and in-use temporal profiles, and opportunities for mobile or at-home protocols that capture real-world experiences.